2016
DOI: 10.3390/ijms17121967
|View full text |Cite
|
Sign up to set email alerts
|

Update on Inflammatory Biomarkers and Treatments in Ischemic Stroke

Abstract: After an acute ischemic stroke (AIS), inflammatory processes are able to concomitantly induce both beneficial and detrimental effects. In this narrative review, we updated evidence on the inflammatory pathways and mediators that are investigated as promising therapeutic targets. We searched for papers on PubMed and MEDLINE up to August 2016. The terms searched alone or in combination were: ischemic stroke, inflammation, oxidative stress, ischemia reperfusion, innate immunity, adaptive immunity, autoimmunity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
114
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 324 publications
(447 reference statements)
3
114
0
6
Order By: Relevance
“…Other indirect effects of smoke derivatives were demonstrated to upregulate cytokines [16], matrix metalloproteinases [38] and adhesion molecules [39] which favour leucocyte-mediated inflammation [40]. neuron-specific enolase, matrix metalloproteinase 9 and malondialdehyde) [46], blood monocyte count is a routine and cheap test that is universally available. monocytes and neutrophils) as well as adhesion molecules when compared to nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other indirect effects of smoke derivatives were demonstrated to upregulate cytokines [16], matrix metalloproteinases [38] and adhesion molecules [39] which favour leucocyte-mediated inflammation [40]. neuron-specific enolase, matrix metalloproteinase 9 and malondialdehyde) [46], blood monocyte count is a routine and cheap test that is universally available. monocytes and neutrophils) as well as adhesion molecules when compared to nonsmokers.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily to other known inflammatory-related biomarker potentially predicting AIS outcome (e.g. neuron-specific enolase, matrix metalloproteinase 9 and malondialdehyde) [46], blood monocyte count is a routine and cheap test that is universally available. Thanks to these features, circulating monocytes might guide the physicians' therapeutic choices even at the emergency department.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic plaques will gradually develop into vascular stenosis and even completely block the cerebral blood flow, leading to an ischemic stroke . Recent researches have confirmed that inflammatory response and various inflammatory factors play an important role in the development of ACI and it has become a research hot spot …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Recent researches have confirmed that inflammatory response and various inflammatory factors play an important role in the development of ACI and it has become a research hot spot. 7,8 Lipoprotein-associated phospholipase A2 (Lp-PLA2), also known as platelet-activating factor acetylhydrolase, is mainly released from atherosclerotic plaque by macrophages and neutrophils. 9 Multiple studies confirm that Lp-PLA2 plays an important role in the process of atherosclerosis and participates in the development of plaque.…”
mentioning
confidence: 99%
“…Little is known about chemokines, small inflammatory molecules classically described to attract circulating inflammatory cells at inflammatory sites . To date, main chemokines for which a pathophysiological role is supposed in IS are as follows: C‐X‐C motif chemokine (CXCL)12, CX3CL1 and C‐C motif chemokine ligand (CCL)2 .…”
mentioning
confidence: 99%